2023
DOI: 10.3390/app13084882
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability of Citrulline in Watermelon Flesh, Rind, and Skin Using a Human Intestinal Epithelial Caco-2 Cell Model

Abstract: Watermelon produces many byproducts (watermelon rind and skin) even though those components contain various bioactive compounds, including citrulline. This study evaluated the citrulline concentration, total phenolic content, and antioxidant activity (DPPH and FRAP assays) of different parts of watermelon and investigated the bioavailability of citrulline from different parts of watermelon using an in vitro human intestinal epithelial Caco-2 cell monolayer model. Solid-phase extracted watermelon flesh, rind, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Moreover, none of the extracts showed toxicity against the studied non-tumor cell line (Vero). According to Lu et al [102], the different parts of watermelon fruit (e.g., flesh, rind and skin) showed a varied efficacy against human intestinal epithelial Caco-2 cells, and they attributed these effects to citrulline content. Moreover, El Gizawy et al [103] reported varied cytotoxic effects of rind extracts of watermelon fruit against human cell lines including A549, Caco-2, H1299, HCT116, Hep2, HepG2, and MCF-7.…”
Section: Cytotoxicitymentioning
confidence: 99%
“…Moreover, none of the extracts showed toxicity against the studied non-tumor cell line (Vero). According to Lu et al [102], the different parts of watermelon fruit (e.g., flesh, rind and skin) showed a varied efficacy against human intestinal epithelial Caco-2 cells, and they attributed these effects to citrulline content. Moreover, El Gizawy et al [103] reported varied cytotoxic effects of rind extracts of watermelon fruit against human cell lines including A549, Caco-2, H1299, HCT116, Hep2, HepG2, and MCF-7.…”
Section: Cytotoxicitymentioning
confidence: 99%